(untitled) (Vietnam Journal of Community Medicine, 2025)
1. Macro hormones are forms of hormones which are larger than normal due to their binding with serum proteins or other components. Macro hormones typically have little to no biological activity. Due to their high molecular weight, macro hormones are not effectively cleared through the kidneys, which can lead to elevated levels in the blood, even though they have little to no biological activity. Additionally, hormone levels in the blood can be abnormally high due to various interference factors, such as binding with heterophile antibodies, medications, or cross-reactivity with other substances. 2. The most common macro hormones are: macroprolactin, macro TSH, macro ACTH, and macro HCG. The false increase of hormones can lead to misdiagnosis or inappropriate treatment by clinicians. Therefore, distinguishing between macro hormone conditions and true increases is necessary. 3. The principle for detecting macro hormones include: polyethylene glycol (PEG) techniques, gel filtration techniques, electrophoresis, and ultrafiltration methods. Each method has its own advantages and disadvantages, with the PEG method being the most commonly used method nowaday